2012
DOI: 10.1002/mrd.22059
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RNA‐binding proteins DND1 and FXR1 in the porcine ovary, and during oocyte maturation and early embryo development

Abstract: The porcine oocyte and early embryo are transcriptionally quiescent following germinal vesicle breakdown in the oocyte and prior to activation of the embryonic genome, at approximately the 4-cell stage of development. Despite a lack of new transcription, mRNA and protein repertoires are subject to regulation during this time. One potential mechanism of regulation is through the functional activity of miRNAs and/or the presence of specific RNA-binding proteins. Both DND1 (dead end homolog 1) and FXR1 (fragile-X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 54 publications
(72 reference statements)
0
26
0
Order By: Relevance
“…Germ cell viability for both male and female and early embryonic development requires DND1 function (Bhattacharya et al 2007 ;Saga 2008 ). We have also demonstrated that DND1 abundance in the maturing pig oocyte and early embryo is greatest during the period of transcriptional quiescence following GVBD and prior ZGA (Yang et al 2012b ). The ability of DND1 to bind specifi c mRNA transcripts associated with pluripotency (POU5F1 (aka OCT4), SOX2, and LIN28) was demonstrated in the germinal vesicle stage oocyte (Yang et al 2012b ).…”
Section: Rna-binding Proteins Impact Mirna Function and Fertilitymentioning
confidence: 57%
“…Germ cell viability for both male and female and early embryonic development requires DND1 function (Bhattacharya et al 2007 ;Saga 2008 ). We have also demonstrated that DND1 abundance in the maturing pig oocyte and early embryo is greatest during the period of transcriptional quiescence following GVBD and prior ZGA (Yang et al 2012b ). The ability of DND1 to bind specifi c mRNA transcripts associated with pluripotency (POU5F1 (aka OCT4), SOX2, and LIN28) was demonstrated in the germinal vesicle stage oocyte (Yang et al 2012b ).…”
Section: Rna-binding Proteins Impact Mirna Function and Fertilitymentioning
confidence: 57%
“…We have also demonstrated that DND1 abundance in the maturing pig oocyte and early embryo is greatest during the period of transcriptional quiescence following GVBD and prior ZGA (Yang et al 2012b ). The ability of DND1 to bind specifi c mRNA transcripts associated with pluripotency (POU5F1 (aka OCT4), SOX2, and LIN28) was demonstrated in the germinal vesicle stage oocyte (Yang et al 2012b ). Considering the numbers of miRNA present in the developing oocyte and the period of oocyte transcriptional quiescence following GVBD, it is possible that DND1 infl uences embryonic developmental competency by contributing to the mRNA and protein repertoire maintenance in the oocyte and early embryo.…”
Section: Rna-binding Proteins Impact Mirna Function and Fertilitymentioning
confidence: 84%
“…Germ cell viability for both male and female and early embryonic development requires DND1 function Saga 2008 ). We have also demonstrated that DND1 abundance in the maturing pig oocyte and early embryo is greatest during the period of transcriptional quiescence following GVBD and prior ZGA (Yang et al 2012b ). The ability of DND1 to bind specifi c mRNA transcripts associated with pluripotency (POU5F1 (aka OCT4), SOX2, and LIN28) was demonstrated in the germinal vesicle stage oocyte (Yang et al 2012b ).…”
Section: Rna-binding Proteins Impact Mirna Function and Fertilitymentioning
confidence: 84%
“…In pig cumulus cells, we found also that the most stable reference genes ( GAPDH/18S ) and expression dynamics of each reference gene during IVM were different from that of pig oocytes. In addition, although mRNA abundance studies in pig cumulus cells have been conducted frequently using HPRT/BACT/GAPDH as single internal control (Blaha, Nemcova, Kepkova, Vodicka, & Prochazka, ; Blaha, Nemcova, & Prochazka, and Yang et al., ), the systematic study on the selection of reference genes has not been performed yet until now. Thus, the combination of GAPDH/18S suitable as references for pig cumulus cells found in the present study could be used in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR is widely regarded as an appropriate strategy to detect and validate mRNA abundance, particularly for samples of small quantities, such as single oocyte (Macabelli et al, 2014), fertilized egg or embryo (Jeong et al, 2005), and even single blastomere (Lindeberg, Hovatta, & Ahrlundrichter, 2004). When studying mRNA abundance of oocyte/embryo samples in different species, several reported methods for total RNA preparation exist, including TRIZOL reagent/RNeasy Kit (Kumar et al, 2012;Mamo, Gal, Polgar, & Dinnyes, 2008), three freeze/thaw cycles with samples in the reverse transcription buffer (Jeong et al, 2005) and Single Cell Lysis Kit (Yang, Wright, & Ross, 2012). Due to limited starting materials, it is impossible or impractical to determine the quality or quantity of prepared total RNA samples regardless of the preparation method.…”
Section: Introductionmentioning
confidence: 99%